Unpublished Chapel of ?y in the Egyptian Museum (CG 1380, 1696, 1699, 1700–01) - Shoaib, Waheid M..
This study concentrates on the original and modified inscriptions and scenes concerning the chapel housed now in the Egyptian Museum (CG 1380, 1696, 1699, 1700–01). The chapel originally belonged to Saqqâra tomb [C 15] of ?y, the wab-priest of Re in the Sun-temple of Sahura, dating to the mid- to late Fifth Dynasty. It was subsequently usurped with royal approval by a woman named Hem(t)re, maybe because of a misdemeanor on his part. It seems likely that he fell into disfavor due to palatial intrigues in the Fifth and Sixth Dynasties, and his tomb was given to Hem(t)re. The artistic merit and technique of the original sculpture are better than those later inserted. Also, the study corrects some doorway blocks which have been wrongly numbered and used by Borchardt for quite other objects.